THE HISTORY OF UK - Xidirova Kamola; Toʻxtayeva Mavluda; Chutboyeva Sohiba (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The article examines the main stages of the history of Great Britain, its socio-economic and political development, as well as the country's role in the global arena. The main periods of Great Britain's history - ancient times, the Middle Ages, the Industrial Revolution and the modern era - are analyzed. The article is written on the basis of scientific sources and reveals the cause-and-effect relationships of historical events.